(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This paper examines the practical application of International Standard on Auditing (ISA) 320, "Materiality in Planning and Performing an Audit," in the context of auditing production costs at the Shurtan Gas Chemical Complex (SGCC), a major industrial enterprise. The study outlines the critical role of ISA 320 in ensuring the reliability and objectivity of the audit opinion, particularly its relationship with ISA 315 on risk assessment. The methodology involves establishing a preliminary materiality level by analyzing key cost components which are identified as high-risk areas for cost allocation and calculation. The paper details the calculation of these materiality levels and discusses the dynamic process of reassessing materiality throughout the audit. The findings confirm that a systematic application of ISA 320 enhances audit efficiency by concentrating resources on significant risk areas, which is essential for complex manufacturing environments like gas-chemical production.